زرعی زمینوں کی ملکیت کے شرعی اسباب: SHARIAH REASONS FOR OWNERSHIP OF AGRICULTURE LAND (Khairulummah, 2023)
In any country, the Shariah status of land and its ownership is very important. Man's survival depends on the land and its production from the time of  Adam (A.S) until now. Man has depended on the production of the land to maintain the relationship between body and soul, while the rest of the Sunnahs are also dependent on the production of the land and its praise. Even in the present age, the great majority is forced to adopt this professon. Because the rest of the creatures get sustenance by simply looking for it and man has to produce his own food.Since land ownership is a fundamental issue that needs elaboration. What was the status of land ownership at the time of holy Prophet SAW? And the legitimate means of land ownership in the light of Quran and Hadith.
Keywords: Shariah; ownership; land; Adam (A.S); Sunnahs